Diversity of Diptera in mixed-used agroforestry area of Tun Razak Agricultural Research Centre, Pahang, Malaysia - PUTERI RAIHANA MEGAT SAHRIR; MUZAMIL MUSTAFFA; NUR AMALINA MOHD IZAM; DZULHELMI MUHAMMAD NASIR; SITI KHAIRIYAH MOHD HATTA; NUR ATHIRAH ABDULLAH (Society for Indonesian Biodiversity, 2024)
Abstract. Sahrir PRM, Mustaffa MB, Izam NAM, Nasir DM, Hatta SKM, Abdullah NA. 2024. Diversity of Diptera in mixed-used agroforestry area of Tun Razak Agricultural Research Centre, Pahang, Malaysia. Biodiversitas 25: 3576-3584. The order Diptera, comprising flies, mosquitoes, midges, and gnats, plays a significant role in the agricultural ecosystem as pests and pollinators. With agricultural activities posing a threat to insect populations globally, there is a need for studies on the potential of managed agroecosystems as habitats for this order. This study provides preliminary information on Diptera diversity in a mixed-used agroforestry area at the Tun Razak Agricultural Research Centre (Pusat Penyelidikan Pertanian Tun Razak/PPPTR), Pahang, Malaysia. The diversity assessment was conducted using malaise traps in various areas within the PPPTR, including a small forest fragment, a rubber plantation, an oil palm plantation, and an orchard, over two weeks in February and March 2023 yielded promising results. A total of 1,077 individuals representing 17 families, 36 genera, and 82 morphospecies of Diptera were collected during the research. The most abundant family recorded was Dolichopodidae, with 429 individuals, followed by Phoridae (140 individuals) and Calliphoridae (130 individuals). Notably, rubber plantations exhibited the highest diversity of Diptera (H'=3.228), while forest fragments showed the lowest diversity (H'=2.745), as indicated by the Shannon-Wiener Diversity Index. These findings highlight the potential of managed agroforestry areas as crucial Diptera conservation habitats, instilling hope and optimism in the scientific community.